Keys to the production office : unlocking success as an office production assistant in film & television - Haire, Jennifer A.; Lobel, Gilana M. (Routledge, 2022)
"Unlocking the door to the very nucleus of a film or television show, this book demystifies the reality of working as an Office Production Assistant. Drawing on over 40 years' combined experience, authors Jennifer A. Haire and Gilana M. Lobel map out a career path into the industry by providing comprehensive practical information designed specifically for individuals pursuing the entry level role of the Office PA. An invaluable tool for both breaking into the industry and on the job, the book is full of detailed "how to" information that not only provides an overview of the full scope of the industry, but also functions as a user's manual for day-to-day working. Haire and Lobel outline variations on the job of an Office PA on both big and small budget feature films and TV shows and how you can be recognised as a vital component of the production team and open the door to your future career. With coverage on phases of a show, the production staff and crew, the practical day-to-day of the office, and developing your career, this is a vital resource for anyone wishing to take their first steps to break into the film and TV industry. Featuring interviews from those in the industry, charts, graphics, diagrams, sample documents, templates, supplemental materials, and light-hearted cartoons throughout the book which immerse the reader into real world scenarios and create a solid foundation for how to be a professional in the workplace. This is an inspiring and practical manual that opens the door to the behind the scenes of film and TV production. It's ideal for aspiring film and TV professionals with little to no experience working in the production office as well as readers studying film and television production courses and industry training programs"--